Toward a Philosophy of the Arabic Dual: A Foundational Study - Darwiche, Frank (Al-Adab Journal, 2025)
This article seeks to establish a new Arabic philosophy: the philosophy of the dual. The goal is not grammatical. There are many grammatical studies on the dual. Rather, it is purely philosophical, beginning with defining this philosophy by reconsidering the origin, moving it from the singular to the dual. This new qualitative shift, which can only happen in a language that values ​​and adopts the dual, gives philosophical thought a distinctive start that opens many doors, some of which are unexpected. It then becomes clear that the singular and the plural must be referred back to the dual. So do time and place – and difference and distance along with them – where neither is superior to the other and they are not separated. The dual also appears, through the successive division it requires, as leading to a ‘ahd (event-epoch) in which man exists in a time and a place, in order to open up to another ‘ahd and to the Other in general in everything that defines such Other in his/her diverse and different affiliations. Man himself appears, in the core of his existence and his recognition of himself, as dual, and from this comes a new composition for the concept of death – death as being-towards-death and as being-after-death, and even death in this life and-after-this-life, with what accompanies such determination, i.e. forms of anxiety, mystery and longing. With the philosophy of the dual, we go beyond archè – any possible overarching principle – as we demonstrate by applying its new approach to Kant’s philosophy, specifically to the categories of the faculty of understanding. The article ends with a call to expand on this philosophy, and promises future studies that address its various aspects.